2020
DOI: 10.1177/0300060520903220
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes: an important messenger in the asthma inflammatory microenvironment

Abstract: Asthma is a frequently diagnosed chronic pulmonary disease that is increasing in incidence. It is characterized by airway narrowing due to an immune response to allergens, infections, or air pollutants. Several types of cells participate in the initiation and development of asthma, including bronchial epithelial cells, smooth muscle cells, and immune cells (mast cells, T and B cells, and dendritic cells). Exosomes released in the asthmatic microenvironment exert a crucial function in intercellular signaling by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
0
15
0
3
Order By: Relevance
“…EVs containing signaling molecules in addition to these miRNAs can be derived from a host of immune cells and respiratory tissue. For example, exosomes from mast cells, T cells, dendritic cells, and eosinophils are associated with promoting the asthma-induced lung inflammatory response 65 , 66 . In addition, EVs that are sourced from fibroblasts can promote smooth muscle tissue and epithelial cell proliferation in severe asthma 67 .…”
Section: Physiological Functions Of Evs In Respiratory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs containing signaling molecules in addition to these miRNAs can be derived from a host of immune cells and respiratory tissue. For example, exosomes from mast cells, T cells, dendritic cells, and eosinophils are associated with promoting the asthma-induced lung inflammatory response 65 , 66 . In addition, EVs that are sourced from fibroblasts can promote smooth muscle tissue and epithelial cell proliferation in severe asthma 67 .…”
Section: Physiological Functions Of Evs In Respiratory Diseasesmentioning
confidence: 99%
“… 21 COPD Endothelial cell-derived EVs are upregulated in the lung. 38 , 39 EV-miR-210 controls autophagy functions and differentiation of my fibroblast 42 Pulmonary hypertension 15-LO2-enriched exosomes trigger proliferation of PAECs by activating STAT3 pathway 47 miR-143-enriched exosomes induce migration and angiogenesis of PAECs, 48 Lung fibrosis EV-bound WNT5A promote lung fibroblast proliferation and pathogenesis of lung fibrosis 50 EVs released from mesenchymal stem cells are involved in repairing damaged tissues 51 Asthma EV-miR-145 is essential to epithelial and smooth muscle cell functions during asthma-induced lung inflammation 56 EVs from mast cells, T-cells, dendritic cells, and eosinophils promote asthma-induced lung inflammation 65 , 66 EVs from fibroblasts promote smooth muscle tissue and epithelial cell proliferation in severe asthma 67 …”
Section: Physiological Functions Of Evs In Respiratory Diseasesmentioning
confidence: 99%
“…Exosomes are believed to play a critical role in the orchestration of immune responses. Previous studies have indicated that cell-derived exosomes could trigger proinflammatory responses by the transportation of molecules contained in the exosomes [7,8]. Additionally, the released exosomes and microRNAs (miRNAs) are detected in bronchoalveolar lavage fluids from patients with respiratory diseases, such as asthma and AR, indicating that exosomes and miRNAs are involved in AR pathogenesis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, asthma is a chronic inflammatory disease induced by allergens and air pollutants that is characterized by airway hypersensitivity and reversible obstruction of airways. Extracellular vesicle miRNAs, like subsets of let-7 and miRNA-200 families, are altered in asthmatics [146,147]. Level of EV miRNAs increases in the epithelium of airways exposed to allergens, particularly miR-223 and miR-142a that have been found to increase in mice treated with allergens [148].…”
Section: Extracellular Vesicles Mediate And/or Antagonize Air Pollution Respiratory Effects and Respiratory Disordersmentioning
confidence: 99%